2015
DOI: 10.1007/s00268-015-3210-6
|View full text |Cite
|
Sign up to set email alerts
|

Complications in Laparoscopic Versus Open Incisional Ventral Hernia Repair. A Retrospective Comparative Study

Abstract: Laparoscopic incisional ventral hernia repair has a low rate of postoperative complications but it is associated with an increased risk of undetected enterotomies, in particular during cases involving adhesiolysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(20 citation statements)
references
References 30 publications
(34 reference statements)
2
16
0
2
Order By: Relevance
“…The study design is shown in Figure 1 . The results of the excluded cases are published in another study [17] .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study design is shown in Figure 1 . The results of the excluded cases are published in another study [17] .…”
Section: Methodsmentioning
confidence: 99%
“…We used the Clavien-Dindo grading system to classify the postoperative complications, which occurred in these patients [16] . The severity of adhesions was graded based on Mueller's classification [17] , that is, grade 0 = no adhesions, grade 1 = simple omental adhesions and grade 2 = intense serosal adhesions.…”
Section: Methodsmentioning
confidence: 99%
“…En los defectos herniarios mayores la técnica de separación de componentes y colocación de malla tipo sublay es el método más descrito, aunque se debe individualizar cada paciente para determinar la mejor técnica quirúrgica (14).…”
Section: Discussionunclassified
“…After the introduction of laparoscopic repair, comparison of laparoscopic and open repair has been questioned by the literature. Although laparoscopic repair promises less pain and faster return to daily activities, these advantages are blamed to be impaired by longer operation time and higher complications such as bowel injury (15). One disadvantage of laparoscopic repair is the higher costs.…”
Section: Discussionmentioning
confidence: 99%
“…Laparoscopic approach was first described by Le Blanc and Booth in 1993 by using intraperitoneal polytetrafluoroethylene (PTFE) mesh (11). This technique has advantages like less pain, scar and seroma formation (12,13) and disadvantages like longer operation time and higher risk of bowel injury (14,15).…”
Section: Introductionmentioning
confidence: 99%